Transparency of the Welfare System and Labor Market Outcomes of Unemployed Workers - Sofie Cairo; Robert Mahlstedt (Institute of Labor Economics (IZA), 2021)
We study how the transparency of welfare systems affects labor market outcomes of unemployed workers in a large-scale field experiment. Our low-cost information intervention uses a personalized online tool that informs benefit recipients about their personal risk of a benefit reduction when not complying with a work requirement. We find disparate effects reflecting individuals' job search status. Providing personalized information improves labor market outcomes by mitigating the pressure to accept unstable part-time jobs among active job seekers with a low sanction risk. Inactive persons with a high sanction risk leave welfare and rely on alternative income support more frequently.
Keywords: J68; D83; C93; 330; unemployment; transfer programs; transparency; sanctions; uncertainty; work requirements; field experiments; information treatment